Exploration of a Contextual Approach Using Areca Nut Media to Optimize Students' Understanding of Mixed Arithmetic Operations in Elementary Schools - Makhali Makhali; Beti Istanti Suwandayani; Agus Tinus (Sakura Digital Nusantara, 2026)
Purpose: This study explored the implementation of a Contextual Teaching and Learning (CTL) approach assisted by areca nut media to improve fourth-grade students’ understanding of mixed arithmetic operations at SD Negeri 2 Waisai during the 2025 academic year in a coastal 3T area where local cultural traditions remain preserved. Methods: This study employed an exploratory qualitative approach involving 28 fourth-grade students, one classroom teacher, and one school principal. Data were collected through classroom observations, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, and conclusion drawing. Findings: The findings revealed that areca nut media improved students’ conceptual and procedural understanding of mixed arithmetic operations, particularly in identifying operational sequences and explaining calculation processes. Students became more active in discussions, collaboration, and problem-solving activities, while their intrinsic motivation toward mathematics increased. The use of familiar local objects enabled students to connect abstract mathematical concepts with daily experiences, making learning more meaningful and engaging. School support through flexible policies and encouragement of local culture-based innovation strengthened the implementation of contextual learning. Research Implications:This study implies that local culture-based media can support meaningful and student-centered mathematics learning, particularly in remote elementary school contexts. However, the findings are limited to one school and one mathematical topic, requiring further studies in broader educational settings. Originality: This study highlights the integration of local wisdom through areca nut media within the CTL approach to support mathematics learning in coastal and remote 3T elementary school contexts.